A copmarative review of electronic prescription systems: Lessons learned from developed countries - Mahnaz Samadbeik; Maryam Ahmadi; Farahnaz Sadoughi; Ali Garavand (Wolters Kluwer Medknow Publications, 2017)
This review study aimed to compare the electronic prescription systems in five selected countries (Denmark, Finland, Sweden, England, and the United States). Compared developed countries were selected by the identified selection process from the countries that have electronic prescription systems. Required data were collected by searching the valid databases, most widely used search engines, and visiting websites related to the national electronic prescription system of each country and also sending E-mails to the related organizations using specifically designed data collection forms. The findings showed that the electronic prescription system was used at the national, state, local, and area levels in the studied countries and covered the whole prescription process or part of it. There were capabilities of creating electronic prescription, decision support, electronically transmitting prescriptions from prescriber systems to the pharmacies, retrieving the electronic prescription at the pharmacy, electronic refilling prescriptions in all studied countries. The patient, prescriber, and dispenser were main human actors, as well as the prescribing and dispensing providers were main system actors of the Electronic Prescription Service. The selected countries have accurate, regular, and systematic plans to use electronic prescription system, and health ministry of these countries was responsible for coordinating and leading the electronic health. It is suggested to use experiences and programs of the leading countries to design and develop the electronic prescription systems.